Pembuatan Aplikasi Penyimpanan Arsip Berbasis Appsheet di Unit Kompensasi dan Benefit PT XYZ - Marsiska, Sophia; Siti Sarah, Ira; Hidya Indira Lastari (MES Bogor, 2025)
This project aims to develop an electronic archive storage application based on AppSheet at the Compensation and Benefits Unit of PT XYZ. In the digital era, manual archive management often leads to challenges in efficiency and data accuracy. Through archive digitization, document search time can be significantly reduced. The method used in this project is the Waterfall method, which includes analysis, design, coding, testing, and maintenance. The implementation results show that this application can enhance archive management efficiency, reduce document search time to less than one minute, and improve data security through role-based access settings. Thus, this application is expected to provide an effective solution for archive management at PT XYZ. Keywords: Archive Storage Application, Digitization, AppSheet, Archive Management, Efficiency.